Methodological Issues &Amp; Strategies in Clinical Research. 1992
DOI: 10.1037/10109-051
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability theory.

Abstract: In this paper we review generalizability (G) theory, a theory of the multifaceted errors of a behavioral measurement. The review was undertaken at the request of Philip Levy, then editor of the Journal.His idea was that the review would commemorate the first article on G theory, which the Journal published in 1963 (Cronbach, Rajaratnam, & Gleser, 1963). For these and personal reasons, we undertook the review. The review does not cover the period 1963-1972 because that has already been done by Cronbach, Gleser,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
139
0
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 27 publications
0
139
0
10
Order By: Relevance
“…In the discussion above, we refer to generalization to different assessors only. 6 We define reliability here in relative, rather than in absolute, terms (see Shavelson & Webb, 1991). required us to average AC ratings (or post exercise dimension ratings, PEDRs) across exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discussion above, we refer to generalization to different assessors only. 6 We define reliability here in relative, rather than in absolute, terms (see Shavelson & Webb, 1991). required us to average AC ratings (or post exercise dimension ratings, PEDRs) across exercises.…”
Section: Discussionmentioning
confidence: 99%
“…To assuage concerns about the number of dimensions and exercises in our study relative to the other examples listed in Table 5, we applied a decision study from generalizability theory methodology, which is akin to applying the Spearman-Brown prediction formula for multifaceted measures (Brennan, 2001;Shavelson & Webb, 1991). Using a decision study, we extrapolated from our observed reliability outcomes based on three exercises and six dimensions to an alternative design based on five exercises and 13 dimensions: the largest number of exercises and dimensions used in the studies listed in Table 5 (i.e., in the Bowler & Woehr, 2009, study).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We also reported median scores since some parameters were not normally distributed. In condition 3 (lengthening and shortening cycles), the systematic difference across cycles was assessed using a type II intra-class coefficient (Shrout and Fleiss, 1979) and standard error of measurement (SEM) (Shavelson, 1991). The purpose of these analyses was to assess which cycles should be averaged in order to have more stable and representative passive parameters of the PFMs.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-rater and test-retest reliability of the subscale scores on the EDE were calculated, whereby generalizability theory was used as a framework for the reliability estimation. 27 The inter-rater generalizability was quite high: Restraint: G ¼ 0.99; Eating concern: G ¼ 0.97; Weight concern: G ¼ 0.97; Shape concern: G ¼ 0.91 and objective bulimic episodes: G ¼ 0.98. The testretest generalizability was very good: Restraint: G ¼ 0.78; Eating concern: G ¼ 0.77; Weight concern: G ¼ 0.61; Shape concern: G ¼ 0.83 and objective bulimic episodes: G ¼ 0.68.…”
Section: Methodsmentioning
confidence: 96%